TRANSITIVITY ANALYSIS ON SRI MULYANI SPEECH AT THE SINGAPORE SUMMIT 2017 - Dede Haryadi; Muhammad Suardi (IKIP Siliwangi, 2018)
Halliday holds that all cultures reflect some universal meta-functions in the languages and proposes three such meta-functions: ideational, interpersonal, and textual. This paper employs the transitivity theory in Halliday’s Systemic Functional Linguistics to analyze on Sri Mulyani’sspeech at The Singapore Summit 2017. Through a quantitative analysis is applied to explore the distribution and functions of six transitivity process in Sri Mulyani’s speech. It is found that among the six processes, material processes (41.8%) highly dominate the speech. Relational processes (30.3%) ranks the second, followed by mental processes (17.2%), behavioral Processes (9.8%) and verbal processes (4.1%), while existential process (0.8%). the writers concludes that the dominate process found in Sri Mulyani’s speech at the singapura summit 2017 is material process with 41.8 %. Halliday holds that all cultures reflect some universal meta-functions in the languages and proposes three such meta-functions: ideational, interpersonal, and textual. This paper employs the transitivity theory in Halliday’s Systemic Functional Linguistics to analyze on Sri Mulyani’sspeech at The Singapore Summit 2017. Through a quantitative analysis is applied to explore the distribution and functions of six transitivity process in Sri Mulyani’s speech. It is found that among the six processes, material processes (41.8%) highly dominate the speech. Relational processes (30.3%) ranks the second, followed by mental processes (17.2%), behavioral Processes (9.8%) and verbal processes (4.1%), while existential process (0.8%). the writers concludes that the dominate process found in Sri Mulyani’s speech at the singapura summit 2017 is material process with 41.8 %.